2014
DOI: 10.1007/s12155-014-9480-2
|View full text |Cite
|
Sign up to set email alerts
|

Side by Side Comparison of Chemical Compounds Generated by Aqueous Pretreatments of Maize Stover, Miscanthus and Sugarcane Bagasse

Abstract: In order to examine the potential for coproduct generation, we have characterised chemical compounds released by a range of alkaline and acidic aqueous pretreatments as well as the effect of these pretreatments on the saccharification ability of the lignocellulosic material. Comparative experiments were performed using three biomass types chosen for their potential as second-generation biofuel feedstocks: maize stover, miscanthus and sugarcane bagasse. The release of lignin from the feedstock correlated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…This could be explained by lignin extraction from the inner regions of the cell wall, and subsequent condensations and redeposition on the surface as reported for wood samples [54]. In comparison with the results from conventional thermo-chemical pretreatment of Miscanthus (180 °C, 40 min) by Gomez et al, and similar amount of lignin is removed by 0.2 M NaOH pretreatment, whereas more lignin (210-240 mg/g biomass) is presented in the biomass after water and 0.2 M H 2 SO 4 pretreatments [50]. Under our conditions, the distribution and structure of lignin could be changed under microwave assisted acidic conditions, and the results show a decreasing lignin amount as measured by using acetyl bromide methods.…”
Section: Effect Of Microwave Assisted Pretreatment On Different Biomasupporting
confidence: 71%
See 1 more Smart Citation
“…This could be explained by lignin extraction from the inner regions of the cell wall, and subsequent condensations and redeposition on the surface as reported for wood samples [54]. In comparison with the results from conventional thermo-chemical pretreatment of Miscanthus (180 °C, 40 min) by Gomez et al, and similar amount of lignin is removed by 0.2 M NaOH pretreatment, whereas more lignin (210-240 mg/g biomass) is presented in the biomass after water and 0.2 M H 2 SO 4 pretreatments [50]. Under our conditions, the distribution and structure of lignin could be changed under microwave assisted acidic conditions, and the results show a decreasing lignin amount as measured by using acetyl bromide methods.…”
Section: Effect Of Microwave Assisted Pretreatment On Different Biomasupporting
confidence: 71%
“…Haverty et al studied peroxide/formic acid assisted pre-treament for Miscanthus under autothermal conditions, and the results showed 0.3-4.37 % cellulose removal across conditions assayed [49]. One of our co-author, Gomez et al studied conventional thermo-chemical pretreatment for Miscanthus material (20-180 °C, holding time 40 min), and their results shows 6-12 mg reducing sugar release/mg biomass (yield from total carbohydrate: 1.88-3.76 %) when temperature is 180 °C [50]. The reducing sugar yield in this work is 19 times higher within half the time than the result from Gomez et al In comparison with other pretreatment methods, our microwave assisted For Miscanthus, microwave assisted pretreatment is therefore more efficient in releasing reducing sugars during pretreatment; the reason could be its unique heating mechanism (magnitude of heating depends on the dielectric properties of the subject) leading to more efficient biomass decomposition.…”
Section: Monosaccharides Analysis In the Pretreatment Mediamentioning
confidence: 99%
“…Consequently, the alkaline pretreatment results in partial extraction of the lignin from the biomass. The acid pretreatment used, on the other hand, hydrolyzes hemicellulosic glycosidic bonds (Gómez et al, 2014). As (di)ferulates link hemicelluloses with lignin, this acid pretreatment also will solubilize part of lignin.…”
Section: Discussionmentioning
confidence: 99%
“…Gomez et al studied conventional heating pretreatment of maize stover. Their results showed that substantial quantities of sugars were released from the biomass by using NaOH or H 2 SO 4 , particularly from hemicellulose fraction [42]. Fig.…”
Section: The Effect Of H 2 Somentioning
confidence: 94%